Influencia de la granulometría y el porcentaje de reemplazo de ladrillo reciclado sobre la resistencia a la compresión, absorción y capilaridad en la fabricación de morteros para enlucidos de albañilería - Bocanegra Mariños, Jahir Andreé (2018)
In this research evaluates the granulometry influence and replacement percentage of recycled brick on the compressive strength, absorption and capillarity in the manufacture of mortars for masonry plastering. Searching alternatives that improve the impact waste brick's as a contaminant on human health and the environment, it is proposed to achieve a more sustainable construction model using recycled brick to produce an alternative mortar with lower production costs and improved the masonry mortars properties. The purpose of this research was to determine the optimum granulometric size and adequate recycled brick's percentage that should replace fine sand in the design of a conventional mortar for plastering mortars. The granulometries evaluated of the recycled brick passed meshes Nº 30, Nº 50 and Nº 100; using replacement percentages of 3, 6, 9, 12, 15 and 18%, with a cement dosage type ICo:fine sand 1: 3 and ratio a/c = 0.80 Shaping and compressive strength mortar test were used 5 x 5 x 5 cm cubes under the ASTM C109 standard, the absorption was determined by ASTM C642 standard and capillarity, ASTM C1585. The specimens were tested at the end of 28 days; except for the compressive strength that were tested at 1, 3 y 7 and 28 days, wich were cured and under environmental conditions. The optimal mortars design with recycled brick was achieved with 18% percentage and a granulometry that passed mesh Nº 100, managing to increase the compressive strength from 244 kg/cm2 to 310 kg/cm2, decrease the absorption from 7.2% to 4.7% and at the same time reduce the capillarity coefficient from 0.0006 g/mm2 x h1/2 to 0.0003 g/mm2 x h1/2.